Design and Development of an Arduino-Based Waste ATM to Promote Public Awareness for Recycling Plastic Waste - Jamas, Agung Rizky; Irwanto, Irwanto; Permata, Endi (The Future of Education Journal, 2025)
This study aims to produce a technology-based innovation product in the form of an Arduino-based Waste ATM that can automatically receive and manage plastic bottle waste to help increase public awareness and participation in recycling waste management. The research method used is research and development or Research & Development (R&D) which adapts the ADDIE development model which consists of 5 (five) stages, namely 1.) Analyze; 2.) Design; 3.) Development; and 4.) Implementation; and 5.) Evaluation. Based on the results of the research that has been carried out, it was found that the Arduino-based waste ATM system has been successfully designed and tested as a solution in automatically managing plastic bottle waste. The implementation of this system uses a capacitive proximity sensor and an ultrasonic sensor that functions to detect the type of material and the volume or size of the waste. In its application, there are several obstacles that need to be considered, such as the setting of the capacitive proximity sensor in recognizing non-plastic waste which causes the system to sometimes be able to process it. Therefore, to improve the effectiveness of the system in supporting public awareness of waste recycling, further optimization is needed such as the integration of additional sensors or the development of more adaptive algorithms.